1998
DOI: 10.1111/j.1467-8624.1998.tb06203.x
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Effects of Prekindergarten Classrooms for Disadvantaged Children on Cognitive Development: The Case of Chapter 1

Abstract: This study explores the effects of the social context of Chapter 1 prekindergarten classrooms on children's learning. Chapter 1 (also called Title I) is a federal government preschool program directed at children in lowincome schools who are at risk of later school failure. Using hierarchical linear modeling (HLM) and a sample of 677 4-year-olds in 55 1990-1991 Chapter 1 prekindergarten classes in 5 states, the study explores factors that influence gains on the Preschool Inventory (PSI) over the preschool year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…The first CTA study and its replication the following year met the expectations that a curriculum unit with a high rating for instructional quality (American Association for the Advancement of Science [AAAS], 2001) would result in positive outcomes overall and significant differences in favour of the new curriculum unit. The ANCOVA analyses showed that students' understanding of the target ideas as measured by the post-test assessment was higher with the new unit and analyses of disaggregated student demographic data (gender, ethnicity/race, socioeconomic status [SES], English language literacy and special education status) showed that subgroups of students learning with the new condition nearly always outscored their peers in the comparison condition (Lynch et al, 2005(Lynch et al, , 2007.…”
Section: Scale-up Ancova Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first CTA study and its replication the following year met the expectations that a curriculum unit with a high rating for instructional quality (American Association for the Advancement of Science [AAAS], 2001) would result in positive outcomes overall and significant differences in favour of the new curriculum unit. The ANCOVA analyses showed that students' understanding of the target ideas as measured by the post-test assessment was higher with the new unit and analyses of disaggregated student demographic data (gender, ethnicity/race, socioeconomic status [SES], English language literacy and special education status) showed that subgroups of students learning with the new condition nearly always outscored their peers in the comparison condition (Lynch et al, 2005(Lynch et al, , 2007.…”
Section: Scale-up Ancova Resultsmentioning
confidence: 99%
“…Further exploratory analysis revealed that students in both treatment and comparison classrooms containing a high percentage of AfricanÁAmericans had lower pretest scores (Figure 3). Lee et al, 1998).…”
Section: Classroom-level Predictorsmentioning
confidence: 99%
See 3 more Smart Citations